In situ establishment of Co/MoS2 heterostructures onto inverse opal‐structured N, S‐doped carbon hollow nanospheres: Interfacial and architectural dual engineering for efficient hydrogen evolution reaction. (9th September 2021) - Lu, Tingyu; Li, Tongfei; Shi, Desheng; Sun, Jialin; Pang, Huan; Xu, Lin; Yang, Jun; Tang, Yawen
Abstract: Rational design of low‐cost and high‐efficiency non‐precious metal‐based catalysts toward the hydrogen evolution reaction (HER) is of paramount significance for the sustainable development of the hydrogen economy. Interfacial manipulation‐induced electronic modulation represents a sophisticated strategy to enhance the intrinsic activity of a non‐precious electrocatalyst. Herein, we demonstrate the straightforward construction of Co/MoS2 hetero‐nanoparticles anchored on inverse opal‐structured N, S‐doped carbon hollow nanospheres with an ordered macroporous framework (denoted as Co/MoS2 @N, S–CHNSs hereafter) via a template‐assisted method. Systematic experimental evidence and theoretical calculations reveal that the formation of Co/MoS2 heterojunctions can effectively modulate the electronic configuration of active sites and optimize the reaction pathways, remarkably boosting the intrinsic activity. Moreover, the inverse opal‐structured carbon substrate with an ordered porous framework is favorable to enlarge the accessible surface area and provide multidimensional mass transport channels, dramatically expediting the reaction kinetics. Thanks to the compositional synergy and structural superiority, the fabricated Co/MoS2 @N, S–CHNSs exhibit excellent HER activity with a low overpotential of 105 mV to afford a current density of 10 mA/cm 2 . The rationale of interface manipulation and architectural design herein is anticipated to be inspirable for the future development of efficient and earth‐abundant electrocatalysts for a variety of energy conversion systems. Abstract : Co/MoS2 hetero‐nanoparticles anchored on inverse opal‐structured N, S‐doped carbon hollow nanospheres with an ordered macroporous framework (Co/MoS2 @N, S–CHNSs) have been developed via a template‐assisted method. Thanks to the compositional synergy and structural superiority, the catalyst exhibits outstanding hydrogen evolution reaction performance.